Aspartyl Aminopeptidase Is Imported from the Cytoplasm to the Vacuole by Selective Autophagy in Saccharomyces cerevisiae - Yuga, Masaki (American Society for Biochemistry and Molecular Biology, 2011)
Macroautophagy is a catabolic process by which cytosolic components are sequestered by double membrane vesicles called autophagosomes and sorted to the lysosomes/vacuoles to be degraded. Saccharomyces cerevisiae has adapted this mechanism for constitutive transport of the specific vacuolar hydrolases aminopeptidase I (Ape1) and α-mannosidase (Ams1); this process is called the cytoplasm to vacuole targeting (Cvt) pathway. The precursor form of Ape1 self-assembles into an aggregate-like structure in the cytosol that is then recognized by Atg19 in a propeptide-dependent manner. The interaction between Atg19 and autophagosome-forming machineries allows selective packaging of the Ape1-Atg19 complex by the autophagosome-like Cvt vesicle. Ams1 also forms oligomers and utilizes the Ape1 transport system by interacting with Atg19. Although the mechanism of selective transport of the Cvt cargoes has been well studied, it is unclear whether proteins other than Ape1 and Ams1 are transported via the Cvt pathway. We describe here that aspartyl aminopeptidase (Yhr113w/Ape4) is the third Cvt cargo, which is similar in primary structure and subunit organization to Ape1. Ape4 has no propeptide, and it does not self-assemble into aggregates. However, it binds to Atg19 in a site distinct from the Ape1- and Ams1-binding sites, allowing it to “piggyback” on the Ape1 transport system. In growing conditions, a small portion of Ape4 localizes in the vacuole, but its vacuolar transport is accelerated by nutrient starvation, and it stably resides in the vacuole lumen. We propose that the cytosolic Ape4 is redistributed to the vacuole when yeast cells need more active vacuolar degradation.